2016
DOI: 10.1590/1806-9061-2015-0135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycyrrhizic Acid on Productive and Immune Parameters of Broilers

Abstract: KeywordsBroiler chickens, growth promotion, immune system, glycyrrhizic acid.Submitted: February/2015 Approved: March/2016 ABSTRACT Considering that glycyrrhizic acid (GRA) has been shown to have in-vitro and in-vivo antiviral activity against a wide range of viruses as well as immunostimulating activity, a trial to evaluate its effects on the performance and the immune response against Newcastle disease of broiler chickens was carried out. The study was performed with oneday-old Ross x Ross broiler chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Al‐Daraji () showed that licorice extract, especially at the level of 450 ppm, effectively diminished the detrimental effects of aflatoxicosis on the general physiological status of broiler chickens. Ocampo et al () suggested that broiler growth performance was improved and mortality was decreased by adding glycyrrhizic acid (the main component of licorice extract) to drinking water via promoting immunity system. In consistent to our results, Nosrati et al () reported that supplementation of Echinacea purpurea extract in broiler’s drinking water increased BWG in grower and total rearing phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al‐Daraji () showed that licorice extract, especially at the level of 450 ppm, effectively diminished the detrimental effects of aflatoxicosis on the general physiological status of broiler chickens. Ocampo et al () suggested that broiler growth performance was improved and mortality was decreased by adding glycyrrhizic acid (the main component of licorice extract) to drinking water via promoting immunity system. In consistent to our results, Nosrati et al () reported that supplementation of Echinacea purpurea extract in broiler’s drinking water increased BWG in grower and total rearing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Vaya, Belinky, and Aviram (1997) isolated several constituents from licorice such as isoflavans (Hispaglabridin A, Hispaglabridin B, Glabridin, and 4-O-Methylglabridin), chalcones (isoprenylchalcone derivative and Isoliquiritigenin) and the isoflavone (Formononetin) with antioxidant capacity. Glycyrrhetinic acid is the main component in licorice, and has been used in human medicine (Ocampo, Gómez-Verduzco, Tapia-Perez, Gutierrez, & Sumano, 2016). It has been showed that licorice has anti-microbial (Fukai et al, 2002), and immunity enhancement effects (Fujioka, Kondou, & Fukuhara, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The active components of licorice and its extracts have anti-inflammatory, immunomodulatory and antiviral functions, and thus can augment the immunity of poultry by modulating both humoral and cell-mediated immune responses, prevent viral diseases, and render supplementary treatment for viral diseases [35,36]. Omer et al [35] reported that LE (60 mg/100 mL Glycyrrhiza extract) when used as a phytogenic feed additive exhibited antiviral activity against the Newcastle disease virus (NDV).…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%
“…This effect has already been reported in chickens. 20,21 Glycyrrhizic acid is known to stimulate gastrointestinal motility and enzyme secretion. 32 Additionally, it has been shown to possess other pharmacological properties including anti-inflammatory, antiulcer, anti-allergic, immune-modulating and antiviral properties.…”
Section: Original Researchmentioning
confidence: 99%
“…In broiler chickens, glycyrrhizic acid stimulates weight gain, and this effect is linked to immune-related effects. 20 This was observed even in chickens affected by infectious bronchitis. 21 Furthermore, glycyrrhizic acid augments the survival of shrimp affected with the viral disease known as white spot syndrome, 22 and again, an Original Research immune-mediated mechanism is proposed.…”
Section: Introductionmentioning
confidence: 98%